Electroporation-mediated replacement of a positively and negatively selectable beta-tubulin gene in Tetrahymena thermophila. - Gaertig, J (1994)
Replacement of lysine-350 by methionine in the beta-tubulin gene of Chlamydomonas confers resistance to microtubule-depolymerizing drugs and increased sensitivity to the microtubule-stabilizing drug taxol. This mutation was created in cloned BTU1, one of two coexpressed beta-tublin genes of Tetrahymena thermophila. When introduced by electroporation, the mutated gene transformed Tetrahymena exclusively by gene replacement at the homologous locus. Taxol-sensitive transformants could be retransformed with a wild-type gene and selection for taxol resistance. Analyses of phenotypic assortment and of the mRNA in transformed cells suggest that complete replacement of the BTU1 gene in the polyploid macronucleus can be obtained. These studies demonstrate the utility of this marker for studying tublin gene function and show that electroporation allows facile gene replacement in Tetrahymena.